2011
DOI: 10.14512/gaia.20.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hospitals: A Socio-Ecological Approach

Abstract: We connect two important societal concerns that are rarely addressed in combination: sustainable development and health promotion. Hospitals as central health care providers can minimize their negative side effects and improve health gain by applying a socio-ecological sustainability concept that focuses on health care -hospitals' core businessand is linked to quality management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…Another leverage point to reduce the health care system's carbon footprint lies in avoiding unnecessary or even harmful treatments and medical interventions or misallocation of patients [10]. For example, avoiding intensive care in hospitals [42] or providing telemedicine solutions can reduce costly and resourceintensive forms of care and at the same time improve health outcomes and quality of life, particularly for people with chronic conditions [43]. Finally, a systemic shift from curative to preventive and from hospital to ambulatory care would likely reduce the health carbon footprint [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another leverage point to reduce the health care system's carbon footprint lies in avoiding unnecessary or even harmful treatments and medical interventions or misallocation of patients [10]. For example, avoiding intensive care in hospitals [42] or providing telemedicine solutions can reduce costly and resourceintensive forms of care and at the same time improve health outcomes and quality of life, particularly for people with chronic conditions [43]. Finally, a systemic shift from curative to preventive and from hospital to ambulatory care would likely reduce the health carbon footprint [1].…”
Section: Discussionmentioning
confidence: 99%
“…When emission reductions directly interfere with core medical services, ensuring the quality of these health care services may be challenging [42]. For example, low carbon procurement strategies require specialized expertise and knowledge about the carbon intensities of different medical products and procedures, the cost effectiveness of different options and a careful consideration of the health effects of alternative treatments [16].…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholder behaviour contributes to the environmental performance of an organisation, especially in terms of waste management for which regulations are in place in most countries (Porter-OʼGrady and Malloch, 2010). Opportunities present that do not deliver direct financial benefits or contribute to legislative compliance, yet make a meaningful contribution to the environment and society, for example, prioritising preventative care where fewer health interventions ultimately reduce associated environmental impacts (Weisz et al, 2011). In a comprehensive review of environmental sustainability in hospitals, McGain and Naylor (2014) identified a need for additional information to guide decision-making, and better inter-disciplinary coordination in research, to deliver more sustainable healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…For early years providers concern with food quality represented an opportunity either to gain a market advantage or improve service user outcomes. To promote activity beyond food quality it was important to identify how a settings approach contributed to core business as expressed, for example, in quality management systems of hospitals (Röthlin et al, 2015;Weisz et al, 2011). For universities there were opportunities to connect food quality to the sector's priorities including student experience and education for sustainable development (Dooris and Doherty, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other settings have received less attention, despite the positive potential for large institutions like hospitals and universities to lever change through the scale of their population reach and purchasing power (Dooris and Doherty, 2010;Weisz et al, 2011). As institutions with a public service dimension, health, education and social care organisations have a significant responsibility for society's most vulnerable are well placed to address social and health disparities.…”
Section: The Settings Approach In Health Promotionmentioning
confidence: 99%